2021
DOI: 10.18805/ag.d-326
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Manures Application on Soil Physicochemical Properties of Coarse-textured Ultisol and Okra Productivity in Nsukka, Southeastern Nigeria

Abstract: Background: The greenhouse and field studies were carried out to assess the effect of different rates of poultry manure (PM), pig slurry (PS) and the recommended NPK fertilizer on some soil physico-chemical properties and okra yield of coarse-textured Ultisols in Nsukka, southeastern Nigeria. Methods: The PM and PS were applied at three different rates (10, 20 and 40 t ha-1) as well as no amendment as control and the recommended NPK fertilizer (300 kg/ha) and replicated five times. Soil and agronomic data coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
2
0
0
Order By: Relevance
“…The findings of the study also, however, indicates that survival strategies of small-scale business such as effective planning, budgeting, and forecasting accounting knowledge and business management techniques, appropriate stock recordkeeping, inventory control of seasonal fluctuation of goods; proper use of advertising media, low price and incentives, elimination of waste, provision of adequate communication and transportation facilities, appropriate leadership development and effective utilization of business resources will facilitate the growth and survival of the small-scale business. This is in agreement with some of the findings of Garba (2005), Azuka (2000) and Ogunna (2009). The study, however, revealed that of the major characteristic of the entrepreneur is the spirit of innovation.…”
Section: Discussion Of Findingssupporting
confidence: 94%
“…The findings of the study also, however, indicates that survival strategies of small-scale business such as effective planning, budgeting, and forecasting accounting knowledge and business management techniques, appropriate stock recordkeeping, inventory control of seasonal fluctuation of goods; proper use of advertising media, low price and incentives, elimination of waste, provision of adequate communication and transportation facilities, appropriate leadership development and effective utilization of business resources will facilitate the growth and survival of the small-scale business. This is in agreement with some of the findings of Garba (2005), Azuka (2000) and Ogunna (2009). The study, however, revealed that of the major characteristic of the entrepreneur is the spirit of innovation.…”
Section: Discussion Of Findingssupporting
confidence: 94%
“…It increased by 138% and 105% for T C12 t/ha and T C8 t/ha respectively. The results are in conformity with (Azuka and Idu., 2021) how found that organic manure improve soil organic matter (Table 5). At 50 DAP, the highest total soil N content was observed for T S YN and T C+SYN with 28 7.6 k g/ha and 267.2 kg /ha respectively (Table 5).…”
Section: Available Soil Nutrientssupporting
confidence: 92%